Meluruskan Makna Nazar: Antara Iman dan Dendam di Tengah Masyarakat Kabupaten Alor - Harun Puling; Jonidius Illu (Jurnal Kala Nea, 2025)
This study aims to examine the transformation of the meaning of vows (nazar) in Alor society from theological and sociocultural perspectives. The main issue addressed in this research concerns the shift in the practice of vows from an expression of commitment of faith to God into a social instrument that is often used to seek revenge or to reinforce group pressure. This study employs a descriptive qualitative method with a fieldwork approach, including in-depth interviews with church and customary leaders, as well as an analysis of biblical texts and anthropological literature on religion. The findings reveal a tension between biblical teachings that emphasize love, forgiveness, and personal commitment, and local customary practices that position vows as instruments of social sanction and symbols of power. In conclusion, the church needs to play an active role in realigning the meaning of vows through contextual congregational education, an inculturation approach, and open dialogue with customary communities. The main recommendation of this study is the development of culturally based pastoral strategies to restore vows as expressions of faith that promote peace and social harmony within Alor society.